2015
DOI: 10.1111/appy.12222
|View full text |Cite
|
Sign up to set email alerts
|

Life events, anxiety, social support, personality, and alexithymia in female patients with chronic pain: A path analysis

Abstract: IntroductionThis study sought to identify a model that explains the relationship between psychosocial factors and chronic pain in female patients, and to explore all of these constructs in a single study and provide a more holistic examination of the overall psychosocial factors that female patients with chronic pain encounter.MethodsFemale patients with chronic pain (n = 147), aged 20–65 (M = 34.9 years, SD = 11.25), from an outpatient pain clinic completed a cross‐sectional self‐report questionnaire on anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…According to Meloni et al ( 2016 ), alexithymia describes the difficulty in identifying and describing emotions and the tendency to minimize emotional experiences and to focus the own attention especially on external stimuli. Several studies reported associations of alexithymia with pain and pain intensity (Aaron et al, 2019 ; Zeng et al, 2016 ), social support (Lumley et al, 1996 ; Saikkonen et al, 2018 ; Zeng et al, 2016 ), insecure attachment styles (Romeo et al, 2020 ), psychosocial stress (Terock et al, 2019 ), dissociation and PTSD (Grabe et al, 2000 ; Terock et al, 2016 ) as well as for hypertension and carotid atherosclerosis (Grabe et al, 2010 ). Similar to resilience, alexithymia is often considered as personality trait (Bagby et al, 2021 ; Gao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Meloni et al ( 2016 ), alexithymia describes the difficulty in identifying and describing emotions and the tendency to minimize emotional experiences and to focus the own attention especially on external stimuli. Several studies reported associations of alexithymia with pain and pain intensity (Aaron et al, 2019 ; Zeng et al, 2016 ), social support (Lumley et al, 1996 ; Saikkonen et al, 2018 ; Zeng et al, 2016 ), insecure attachment styles (Romeo et al, 2020 ), psychosocial stress (Terock et al, 2019 ), dissociation and PTSD (Grabe et al, 2000 ; Terock et al, 2016 ) as well as for hypertension and carotid atherosclerosis (Grabe et al, 2010 ). Similar to resilience, alexithymia is often considered as personality trait (Bagby et al, 2021 ; Gao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Therefore, individuals with chronic pain should undergo psychotherapeutic treatment that enable them to break down this vicious circle by improving their ability to detect and distinguish emotions and bodily sensations. 20,35 The importance to consider psychotherapy also relies on the fact alexithymia could result in hypervigilance, increasing somatic sensations and inducing high levels of depression. 36,37 Alexithymia could exacerbate depressive symptoms and pain through the misinterpretation of bodily sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Esta relación podría comprenderse mediante los modelos holísticos que establecen los eventos de la vida como un mediador en la relación entre factores de la personalidad, el apoyo social percibido y el dolor crónico. Los factores sociales y psicológicos son importantes para explicar el dolor crónico en los pacientes 25 . Debido a las características de este trabajo no es posible determinar si el dolor crónico es un factor previo o posterior al acontecimiento de la separación, pero existen estudios que vinculan el inicio del padecimiento de dolor con un incremento en la tasa de divorcios cuando el miembro de la pareja es de sexo femenino 26 .…”
Section: Discussionunclassified